1991
DOI: 10.1099/0022-1317-72-10-2347
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence analysis and genomic organization of the NY-RPV isolate of barley yellow dwarf virus

Abstract: cDNA clones representing the ssRNA genome of the NY-RPV isolate of barley yellow dwarf luteovirus (BYDV) were sequenced and 5600 nucleotides of the genome were determined. The deduced genome organization has limited similarity to that of another BYDV isolate, Vic-PAV, but is identical to that of beet western yellows (BWYV) and potato leafroll (PLRV) luteoviruses. NY-RPV has six major positive-sense open reading frames (ORFs) and, by comparison with RNA-dependent RNA polymerase and nucleic acid helicase consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 37 publications
(66 reference statements)
0
45
0
2
Order By: Relevance
“…4;Hodgman, 1988;Habili & Symons, 1989;Koonin, 1991). Based on the occurrence and arrangement of these motifs, it has been proposed that this group of viruses constitutes a separate taxonomic entity, different from the PLRV-BWYV subgroup of the tuteoviruses which also contains the NY-RPV isolate of BYDV and RNA 1 of PEMV (Habili & Symons, 1989;Koonin, 1991;Vincent et al, 1991). Consistent with this model is the observation that this 65K product does not display homology with the polymerase cassette of PEMV RNA 1, nor with its allied luteoviruses.…”
Section: Analysis Of the 65k Orfmentioning
confidence: 99%
“…4;Hodgman, 1988;Habili & Symons, 1989;Koonin, 1991). Based on the occurrence and arrangement of these motifs, it has been proposed that this group of viruses constitutes a separate taxonomic entity, different from the PLRV-BWYV subgroup of the tuteoviruses which also contains the NY-RPV isolate of BYDV and RNA 1 of PEMV (Habili & Symons, 1989;Koonin, 1991;Vincent et al, 1991). Consistent with this model is the observation that this 65K product does not display homology with the polymerase cassette of PEMV RNA 1, nor with its allied luteoviruses.…”
Section: Analysis Of the 65k Orfmentioning
confidence: 99%
“…The product encoded by the MAV-PS10RF6 is 4.3K and that of P-PAV ORF6 is 6.5K. The genome organization of these BYDV isolates is similar to that described for Vic-PAV (Miller et al, 1988), yet different from that of BYDV (NY-RPV) (Vincent et aL, 1991). As such, for MAV-PS1, P-PAV and Vic-PAV, ORFs l and 2 are proposed to encode the viral replicase, ORF3 the coat protein and, based on the identification of a 17K genome-linked small protein (VPg) from a BYDV (RPV) isolate (Murphy et al, 1989), ORF4 putatively encodes the VPg.…”
Section: Gg CC Aaau Aggu Agac Uc Cu Caacau Cggaac Cgcaac C U Gcac Cagmentioning
confidence: 72%
“…In fact, the transcriptional start site of a 2.6 kb subgenomic RNA from PLRV has recently been mapped to 34 nucleotides 5' of the coat protein translation initiation codon (Tacke et al, 1990) and corresponds to a conserved region identified in all other published luteovirus sequences (Vincent et al, 1991). Between MAV-PS1 and P-PAV there is 91~ sequence identity for the coat protein leader sequences; for P-PAV and Vic-PAV this region has 99~ identity.…”
Section: Gg CC Aaau Aggu Agac Uc Cu Caacau Cggaac Cgcaac C U Gcac Cagmentioning
confidence: 99%
See 2 more Smart Citations